2009
DOI: 10.1002/smi.1269
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic events, perceived stress and health in women with fibromyalgia and healthy controls

Abstract: SummaryThis study examined the relationship between trauma, stress and health in 41 women with fi bromyalgia (FM) and 44 women who were healthy controls (HC). The participants were assessed for traumatic events, perceived stress and mental and physical health. Perceived stress was related to worse mental and physical health in both groups. Traumatic events were related to worse mental and physical health in the FM group but were unrelated to health in the HC group. Perceived stress partially mediated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…As far as empirical evidence is concerned, a plethora of cross-sectional studies have used questionnaires measuring chronic stress or daily hassles in patients with FMS. In these studies, the magnitude of self-reported stress was linked to pain severity and/or functional impairment (Alok et al, 2011;Dailey et al, 1990;Murray et al, 2007;Smith et al, 2010). These findings suggest that stress can indeed exacerbate symptoms in patients with FMS.…”
Section: Introductionmentioning
confidence: 87%
“…As far as empirical evidence is concerned, a plethora of cross-sectional studies have used questionnaires measuring chronic stress or daily hassles in patients with FMS. In these studies, the magnitude of self-reported stress was linked to pain severity and/or functional impairment (Alok et al, 2011;Dailey et al, 1990;Murray et al, 2007;Smith et al, 2010). These findings suggest that stress can indeed exacerbate symptoms in patients with FMS.…”
Section: Introductionmentioning
confidence: 87%
“…Smith et al (2010) showed that FM patients had a higher prevalence of childhood emotional abuse (58.5% v. 18%) when compared with controls, and Kosseva et al (2010) found that 16% of FM patients reported experiencing severe childhood emotional abuse. Lastly, Tietjen et al (2010) demonstrated that a large percentage of patients with FM had a history of childhood emotional abuse (54%).…”
Section: Childhood Emotional Abusementioning
confidence: 96%
“…Among these, six were case-control studies. Three studies reported a higher incidence of childhood sexual (range 7-37% v. 6-22%) and physical abuse (range 8-34% v. 4-12%) in FM patients than in controls (Boisset-Pioro et al 1995;Ruiz-Perez et al 2009;Smith et al 2010). Anderberg et al (2000) also demonstrated that FM patients had a higher prevalence of childhood sexual (7.5% v. 5%) and physical or psychological abuse (27.5% v. 13%) than patients without a history of abuse.…”
Section: Childhood Sexual and Physical Abusementioning
confidence: 96%
“…It has been well documented that stress‐related health concerns are associated with increased health care costs, disability and absenteeism at the workplace. Having a high level of perceived stress has been found to be associated with poor overall quality of life in a sample of over 13,000 employees (Clark et al, in press) and in a sample of women with fibromyalgia and in healthy controls (Smith et al, ), and reducing stress has been found to improve the quality of life of adults (Nyklicek & Kuijpers, ). It has been estimated that two‐thirds of the general population has experienced stress within the past 2 weeks, with almost 50% rating their stress as ‘moderate’ or ‘high’ (Williams, Kolar, Reger, & Pearson, ).…”
Section: Introductionmentioning
confidence: 99%